Differences in the Genomic Profiles of Immunoparalyzed and Nonimmunoparalyzed Children With Sepsis: A Pilot Study*. Issue 2 (February 2022) - Farhat, Mohamed Hani; Shadley, Jeffery D.; Halligan, Nadine L. N.; Hall, Mark W.; Popova, Antonia P.; Quasney, Michael W.; Dahmer, Mary K.
Abstract : OBJECTIVES: Sepsis-induced immunoparalysis represents a pathologic downregulation of leukocyte function shown to be associated with adverse outcomes, although its mechanisms remain poorly understood. Our goal was to compare genome-wide gene expression profiles of immunoparalyzed and nonimmunoparalyzed children with sepsis to identify genes and pathways associated with immunoparalysis. DESIGN: Prospective observational study. PATIENTS: Twenty-six children with lower respiratory tract infection meeting criteria for sepsis, severe sepsis, or septic shock admitted to the PICU. SETTING: Two tertiary care PICUs. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Innate immune function was assayed ex vivo by measuring release of tumor necrosis factor-α from whole blood after incubation with lipopolysaccharide for 4 hours. Immunoparalysis was defined as a tumor necrosis factor-α production capacity less than 200 pg/mL. Ten of the 26 children were immunoparalyzed. There were 17 significant differentially expressed genes when comparing genome-wide gene expression profiles of immunoparalyzed and nonimmunoparalyzed children (false discovery rate < 0.05). Nine genes showed increased expression in immunoparalyzed children (+1.5- to +8.8-fold change). Several of these dampen the immune system. Eight showed decreased expression in immunoparalyzed children (–1.7- to –3.9-fold change), several of which are involved in early regulation and activation of immune function. Functional annotation clustering using differentially expressed genes with p value of less than 0.05 showed three clusters related to immunity with significant enrichment scores (2.2–4.5); the most significant gene ontology terms in these clusters were antigen processing and presentation and negative regulation of interleukin-6 production. Network analysis identified potential protein interactions that may be involved in the development of immunoparalysis in children. CONCLUSIONS: In this exploratory analysis, immunoparalyzed children with sepsis showed increased expression of genes that dampen the immune system and decreased expression of genes involved in regulation and activation of the immune system. Analysis also implicated other proteins as potentially having as yet unidentified roles in the development of immunoparalysis. Abstract : Supplemental Digital Content is available in the text.